PENGARUH TEKNIK RELAKSASI OTOT PROGRESIF TERHADAP TINGKAT KELELAHAN ANAK DENGAN KANKER POST KEMOTERAPI - Utami, Kadek Cahya; Puspita, Luh Mira (Coping: Community of Publishing in Nursing, 2023)
Chemotherapy is one of the most effective therapies for pediatric cancer. In addition to its therapeutic effects, chemotherapy can also have side effects on children with cancer. Fatigue is one of the problems children with cancer which can affect the child's quality of life. Various non-pharmacological interventions are recommended to reduce the level of fatigue in children with cancer. In this regard, the aim of the present study was to investigate the effectiveness of progressive relaxation techniques on the level of fatigue in post chemotherapy cancer children. This study was a quasi-experimental with a total sampling technique. The sample of the present study consisted of 30 children. The results showed that there was a significant difference in children's fatigue scores before and after being given the intervention (p=0,001), so it can be concluded that progressive relaxation techniques can reduce the level of fatigue in children with cancer who receive chemotherapy. Therefore, it is recommended for nurses and families will be able to implement this intervention while the patient is being treated in hospital or at home.